The Effect of Ophiocephalus Striatus Extract on suPAR, Neutrophil Levels and Lung Diffusion Capacity (DLCO) in Stable Chronic Obstructive Pulmonary Disease (COPD) Patients with Muscle Wasting - Sasongko Adhi Nugroho; Teguh Rahayu Sartono; Susanthy Djajalaksana; Harun Al Rasyid (Jurnal Respirologi Indonesia, 2019)
Background: Muscle wasting is one of the extrapulmonary manifestation which influence quality of life in Chronic Obstructive Pulmonary Disease (COPD) patients. It caused by imbalance of protein metabolism in skeletal muscle. This study aimed to evaluate the effect of Ophiocephalus striatus extract on neutrophil count, soluble urokinase-type plasminogen activator (suPAR) level, diffusion capacity of lung for carbon monoxide (DLCO) and quality of life in stable COPD patients with muscle wasting. Methods: Clinical pre and post quasi experimental study was conducted to 32 stable muscle-wasted COPD patients from Pulmonary Outpatient Clinic Saiful Anwar Hospital Malang, determined by The Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2016, Bioelectrical impedance analysis (BIA) dengan fat-free mass (FFM)